36=2(x-5)

Simple and best practice solution for 36=2(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=2(x-5) equation:


Simplifying
36 = 2(x + -5)

Reorder the terms:
36 = 2(-5 + x)
36 = (-5 * 2 + x * 2)
36 = (-10 + 2x)

Solving
36 = -10 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
36 + -2x = -10 + 2x + -2x

Combine like terms: 2x + -2x = 0
36 + -2x = -10 + 0
36 + -2x = -10

Add '-36' to each side of the equation.
36 + -36 + -2x = -10 + -36

Combine like terms: 36 + -36 = 0
0 + -2x = -10 + -36
-2x = -10 + -36

Combine like terms: -10 + -36 = -46
-2x = -46

Divide each side by '-2'.
x = 23

Simplifying
x = 23

See similar equations:

| 2Y(0.5x)=x-4 | | 12+4n=24+6n | | Z=-8i | | 3x-15+x=5 | | 0.2x^2-0.4x-1=1-3x | | 10-6y=12-8y | | 5y=x^2-2x-5 | | 4x+5=-21-5x | | 3.2p+4=2p-2 | | 3.2+4=2p-2 | | 6x-1=5(x+1) | | 14x+y=3*14 | | 2x+3-4=8x+3 | | y=(4sinx)(8cosx) | | 24/(4/3) | | 5*ln(2a-1)=15 | | x^4-6x^3+4x^2-24x=0 | | 3x^2-13(x-y)+4=0 | | (2/7)x=42 | | 3x^2y^2-13x-13y+4=0 | | 2x(x+1)=5-2x | | .05x+.1y=1 | | 0=3x^2-18-48 | | 9n+11=65 | | 2y+18+5y= | | 5x+10=8x | | 3x^4-4x^3+3=0 | | 7secx+7tanx=7 | | 5n-3+2n+6=3n+4-7n-9 | | 3(2x-6)=6(2x+1) | | 4+8=48 | | 6+6*6-6+6= |

Equations solver categories